IMF Staff papers : Volume 31 No. 2. (IMF Staff Papers; IMF Staff Papers ;, 1984)
This paper examines the validity of the hypothesis that the level of the real wage rate, inclusive of employers' expenditures for social insurance and employment or payroll taxes, is a major obstacle to a return to high employment in industrial countries. The hypothesis is tested by estimating a production function, solving it for the real wage rate that would be consistent with the high-employment level of labor input given the existing capital stock, and comparing this warranted wage with the actual real wage. The disequilibrium real wage rate hypothesis is based largely on the observation that, at least in manufacturing, the real wage rate defined from the employer's standpoint-that is, the nominal wage rate deflated by the value-added deflator rather than by the consumer price index-has tended to grow faster than labor productivity during the past decade and a half. Voluntarily or as a result of government regulation, firms purchase equipment that produces products that are omitted from the measured gross national product (GNP).